(untitled) (Quinto Sol, 2023)
This paper intends to analyze an episode in the life of Ignatian cult objects that had been used to house churches and schools of the order in the River Plate territory. Our protagonists will be images and objects of worship that once had a special significance due to their centrality in composing the liturgy and their proximity to the sacred. Despite their heterogeneity, all these objects, made of rich metals, had formed a River Plate Jesuitical material culture that had exalted the identity of the order. From a perspective focused on material culture, we will analyze how, once the process of managing temporalities began, these objects traveled an unsuspected path that altered their biographies, their symbolic meanings, and their valuations as sacred goods. From then on, desacralized and defunctionalized, these pieces went through processes of embargoes, commodification and disputes over their possession until their subsequent disappearance. Recomposing these paths will allow us to demonstrate the importance that these objects had in composing worship and liturgy followed by historical processes that led to one of the largest looting and diasporas of artistic heritage in the 18th century within the framework of its growing desecration.